Pregled kamenog oruđa i oružja iz Vince - Srejović, Dragosalv (Arheološki vestnik, 1957)
This is the first publication about stone implements and arms found during the systematic excavation made by Prof. M. M. Vassits in Vinca from 1929 to 1934. The entire materials excavated at the site are in keeping of the Archaeo[1]logical collection of the University of Belgrade. This survey is based upon 5689 objects of stone, divided into three fundamental groups according to the material of which the objects are made: I. Obsidian implements (1398 objects found) appear from V 10,15 to V 3.8 m cultural layer of Vinca (T-1—II) as knives and scrapers. The majority of ob[1]sidian objects was found between V 8,6 and V 8,0m (54,9 %). II. Flint implements and arms (1748 objects found) appear in Vinca from V 10,5 to V 2,0 m (T. Ill—VI). There were found the same formis as in the obsidian objects. The culminating point of the flint industry in Vinca is between V 7,0 and V 6,0 m (see graph 1). IIT. The implements and arms of different sedimentai and volcanic stones (543 objects found) were used from the foundation of Vinca to the end of the settlement (from V 10,5 to \7 0,0m). In the oldest place with burrows the use of such objects is rare (0.9 %o). The greatest quantity of the objects was found between V 7,0 and V 6,0 nr (31,9%) but above V 4.0 m the use of ]X>lished storne objects gradually disappears. One can differentiate 8 main types (T. XXV, A—D; T. XXVI, D, E, F, H). The type A appears between V 9,1 and V2,5m (T. VII, 2; T. XI, 44; T. XX, 145; T. XXI, 161), type Bi between V 10,10 and V 2,5 (4,1) m (T. VII, 1; T. XXIII, 176; T. X, 37, T. XX, 144), type Ba between V 9,1 and V 2,2 m (T. VII, 4; T. XV, 87; T. XXI, 163), type Ci between V 8,9 and V 4,8 m (T. VIII, 14; XVI, 108), type Cs between V 8,5 and V 5,1 m (T. VII, 7; T. XVII, 115), type Di between V 7,8 and V 4,9 m (T. XI, 39; XIV, 77, 78; XXI, 156), type Da between V 7,4 and V 4,6 (T. X, 54, 35; XXI, 159), type Ei between V 8,4 and V 5,7 m (T. VIII, 16, 19; T-IX, 21; T. XIX, 129, 130), type E2 between V 8,4 (8,9) and V 4,4 m (T. VIII, 13; IX, 22; XI, 41; T. XIV, 79), type F between V 8,15 and V 2,7 (4,5) m (T. VIII, 15), type G (bored hammg) between V 6,9 and V 0,0 m (T. XV, 83; T. XIX, 128; T. XX, 146, 147, 148; T. XXII, 165—168, 171; T. XXIII, 182—184, 178—180; T. XXIV, 181 182, 184), type Hi between V 7,3 and V 6,9 m (T. XI, 45) and type H2 between V 6,1 and V 5,1 m (T. XVIII, 120). Separate groups are the disk-shaped mace (between V 10.10 and V 8,5 m; T. XXVII, A—B), the stone rings (between V 9,0 and V4,9m; T. XXVII I—9) and the mace-heads (between V 7,1 and V 0,9 m; T. XV, 85, 86; T. XXIV, 185). On the basis of a statistical survey of stone arms and implements from Vinca, according to the material, types and stratigraphy, one can draw the foilwing conclusions: At the time of the first settlement in Vinca (V 10>5—y 9,0 m) there were all the main materials for the implements (obsidian, flint and stone) but their use at that time was rare. In the second place (the layer of the buil[1]dings with a rectangular base between V 9,0 and V 8,0 m) there was an abrupt increase of obsidan (54,9 %). The use of polished stone and flint implements does not occur until the appearance of the earlier settlement (between V 7,0 and V 6,0 m). After V4,0m the number of all types of implements abruptly diminishes allowing for the supposition that there were some deep changes in pro[1]ductive relation and in the culture of Vinca the V 4.0 m.